Thoracoscopic lobectomy after neoadjuvant chemoimmunotherapy for lung cancer: a systematic review and meta-analysis - Bochkova, Jacqueline; Gao, Dylan; Suvarna, Chetana; Kumari, Aditi; Wassertzug, Deborah; Kumar, Prashanth A.; Ely, Sora (Video-Assisted Thoracic Surgery, 2026)
Thoracoscopic surgery, both video-assisted thoracoscopic surgery (VATS) and robot-assisted thoracoscopic surgery (RATS), has superior outcomes compared to open thoracotomy, particularly improved perioperative outcomes. However, since the recent advent of neoadjuvant chemoimmunotherapy (chemoIO) for non-small cell lung cancer (NSCLC), the safety and efficacy of thoracoscopic lobectomy in this setting are largely unknown. We conducted a systematic review and meta-analysis to evaluate available outcomes data for thoracoscopic lobectomy after chemoIO for NSCLC.